2017
DOI: 10.1021/acs.jafc.7b02282
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol Suppresses Mylip/Idol Gene Expression and Modulates LDLR Abundance and Activity in HepG2 Cells

Abstract: Xanthohumol, a prenylated flavonoid found in hops (Humulus lupulus L.), exhibits multiple biological activities such as antiatherosclerosis and hypolipidemic activities. In this study, we aim to investigate the hypocholesterolemic effects and molecular mechanisms of xanthohumol in hepatic cells. We found that xanthohumol (10 and 20 μM) increased the amount of cell-surface low-density lipoprotein receptor (LDLR) from 100.0 ± 2.1% to 115.0 ± 1.3% and 135.2 ± 2.7%, and enhanced the LDL uptake activity from 100.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…In this respect, several natural compounds have been tested for their synergistic effects with statins. The results showed that PCSK9 inhibitors such as curcumin, epigallocatechin gallate, and tanshinone IIA, and IDOL inhibitor such as xanthohumol enhanced the statin-mediated induction of LDLR mRNA and LDL-C uptake 16,[48][49][50] . In the present study, we demonstrated that co-treatment of HepG2 cells with PD and simvastatin resulted in further increase in LDLR expression and LDL-C uptake compared to simvastatin alone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this respect, several natural compounds have been tested for their synergistic effects with statins. The results showed that PCSK9 inhibitors such as curcumin, epigallocatechin gallate, and tanshinone IIA, and IDOL inhibitor such as xanthohumol enhanced the statin-mediated induction of LDLR mRNA and LDL-C uptake 16,[48][49][50] . In the present study, we demonstrated that co-treatment of HepG2 cells with PD and simvastatin resulted in further increase in LDLR expression and LDL-C uptake compared to simvastatin alone.…”
Section: Discussionmentioning
confidence: 98%
“…We also found that PD reduced the IDOL mRNA expression induced by synthetic LXR agonist T0901317, demonstrating that PD inhibits the LXR-dependent IDOL gene expression. The LXR-IDOL pathway can be inhibited by down-regulation of LXR expression 38,39 or competitively inhibiting LXR agonist binding into the ligand-binding pocket of LXR protein 16 . Our data showed that LXRα expression was not changed by PD, suggesting that PD may antagonize LXR transcriptional activity without affecting LXR expression.…”
Section: Discussionmentioning
confidence: 99%
“…▶ Table 3 Percentage of prenylated hops compounds (1)(2)(3)(4)(5) in investigated samples (Prod1-6) (n = 3) determined via quantitation using the PDA signal at 220 nm. The calculated recommended daily intake of reference substances in μg per dietary product (Prod1-4) is given in parentheses.…”
Section: Standards Samples and Solventsmentioning
confidence: 99%
“…Apart from this, a considerable number of pharmacological research studies has been conducted on hop strobile and its constituents regarding estrogenic activities, anticancer properties, and anti-inflammatory effects [3][4][5]. Some of these results have been…”
Section: Introductionmentioning
confidence: 99%
“…Instantaneous adenoviral overexpression of mouse IDOL gene in wildtype model resulted in a significant decrease in LDLR protein and an increase in LDL-C levels 9 , 10 . Other possible downstream of IDOL includes VLDLR and ApoER2 11 . The upstream of IDOL is LXRs which have influence on extracellular cholesterol levels by combining with LXR element of IDOL 12 .…”
Section: Introductionmentioning
confidence: 99%